Religious Environmental Activism in Asia: Case Studies in Spiritual Ecology - Sponsel, Leslie E. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Throughout the world religious organizations are exploring and implementing into action ideas about the relevance of religion and spirituality in dealing with a growing multitude of environmental issues and problems. Religion and spirituality have the potential to be extremely influential for the better at many levels and in many ways through their intellectual, emotional, and activist components. This collection focuses on providing a set of captivating essays on the specifics of concrete cases of environmental activism involving most of the main Asian religions from several countries. Particular case studies are drawn from the religions of Animism, Buddhism, Daoism, Hinduism, Islam, and Jainism. They are from the countries of Bhutan, China, India, Indonesia, and Thailand. Thereby this set of case studies offers a very substantial and rich sampling of religious environmental activism in Asia. They are grounded in years of original field research on the subjects covered. Collectively these case studies reveal a fascinating and significant movement of environmental initiatives in engaged practical spiritual ecology in Asia. Accordingly, this collection should be of special interest to a diversity of scientists, academics, instructors, and students as well as communities and leaders from a wide variety of religions, environmentalism, and conservation.